The Crime of Genocide in Theory and Practice: International and Criminal Law of Bosnia & Herzegovina - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
International criminal law, as a system of legal rules contained in the documents of the international community and in the documents of national (internal) criminal law, provides for criminal liability and punishment for a great number of international crimes (such as genocide). These crimes are acts of breaking war laws and rules of warfare (international humanitarian law), and also they are acts of harming or imperilling the peace among nations and the security of mankind. For these acts there are provided most severe penalties and measures of punishment known in the criminal law today. The penalties prescribed for these criminal offences are among the most severe in contemporary criminal legislation. For perpetrators of these crimes of genocide, in certain cases, the primary jurisdiction is that of international criminal court (supra-national) authorities, such as the International Court in The Hague. In this paper, the author has analysed the notion and basic characteristics of the crime of genocide in international and criminal law of Bosnia and Herzegovina.